2015
DOI: 10.1111/jgs.13795
|View full text |Cite
|
Sign up to set email alerts
|

Medications That Older Adults in Hospice Care in the United States Take, 2007

Abstract: People continue to receive disease-focused therapies at the end of life rather than therapies exclusively for palliation of symptoms, suggesting that treatments may vary according to the person's primary diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
(54 reference statements)
0
29
1
Order By: Relevance
“…It may be relevant that close to 70% of hospice patients were taking an opiate and an anxiolytic or hypnotic in the last week of life 118 . This is not evidence by itself whether this combination influences the survival of hospice patients, nor is the author commenting on the ethics of combining such drugs in a genuine hospice situation.…”
Section: Contributory Factors Combined With Hypnotics Could Cause Covmentioning
confidence: 99%
“…It may be relevant that close to 70% of hospice patients were taking an opiate and an anxiolytic or hypnotic in the last week of life 118 . This is not evidence by itself whether this combination influences the survival of hospice patients, nor is the author commenting on the ethics of combining such drugs in a genuine hospice situation.…”
Section: Contributory Factors Combined With Hypnotics Could Cause Covmentioning
confidence: 99%
“…Prescribing medications may be particularly challenging during the transition from acute care hospital settings to hospice care because of the often abrupt shift in goals of care and changes in underlying indications for medication use. This is significant because nearly 40% of hospice patients are referred to hospice care from an acute care hospital, and previous large studies suggested that hospice patients receive an average of 10 to 16 medications including several medications with unclear indications in the hospice setting (eg, statins, antithrombotic therapy, and antibiotics) …”
mentioning
confidence: 99%
“…A total of 12 studies were found to meet the inclusion criteria and were included in the review. (Table 1) Studies were conducted in nine different countries, with one study analysing data from 11 different European countries -Austria (n = 1) [17], Brazil (n = 1)(18), Canada (n = 1) [19], Germany (n = 1) (17), Italy (n = 2) [20,21], Netherlands (n = 2) [4,22], Norway (n = 1) [23], Switzerland (n = 1) [17] and USA (n = 3) [3,24,25]. The multinational study reported on medication use in Norway, Italy, Germany, the UK, Iceland, Sweden, Switzerland, Lithuania, Denmark, Finland and Greece [26].…”
Section: Resultsmentioning
confidence: 99%
“…It is apparent that there is a significant lack of published literature outlining drug usage in palliative care settings. However, three quarters (9/12) of the articles reviewed were published in the last 9 years (date range: 2011-2016) [3,4,18,[21][22][23][24][25][26]. The majority of studies used a retrospective means of data extraction [3,4,[19][20][21][23][24][25][26] and ranged in duration from 3 months to 5 years.…”
Section: Resultsmentioning
confidence: 99%